Multiple time series models - Brandt, Patrick T.; Williams, John T. (John Taylor), 1958- (Thousand Oaks, [Calif.] ; London : SAGE, 2007)
A comprehensive introduction to multiple time series in the social sciences, this book places multiple time series into historical context and then introduces structural equation modeling, vector auto regression (VAR), and factor analytic techniques for analysing multiple time series.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Time-series analysis -- Mathematical models